The Power of Collaborative Planning: How a Health and Planning Collaboration Facilitated Integration of Health Goals in the 30-Year Plan for Greater Adelaide. Issue 3 (2nd July 2020) - McGreevy, Michael; Harris, Patrick; Delaney-Crowe, Toni; Fisher, Matt; Sainsbury, Peter; Baum, Fran
ABSTRACT: This article examines the relationship between theories of urban governance, strategic planning and collaborative planning and the preparation of a strategic spatial plan for the greater Adelaide region. In particular, it analyses the extent to which health professionals involved in the collaborative processes used to formulate the plan were able to advocate for health-related objectives. The analysis was undertaken using data collected in interviews with actors directly involved in the collaborative processes that produced the plan. Interview responses were analysed to understand how factors that can derail or conversely facilitate successful collaborative planning processes were dealt with.